Flora & Ulysses : The Illuminated Adventures - DiCamillo, Kate.; Campbell, K. G. (Keith Gordon), 1966- (Somerville, Mass. : Candlewick Press, 2013)
Rescuing a squirrel after an accident involving a vacuum cleaner, comic-reading cynic Flora Belle Buckman is astonished when the squirrel, Ulysses, demonstrates astonishing powers of strength and flight after being revived.
Keywords: Squirrels -- Juvenile fiction; Superheroes -- Juvenile fiction; Squirrels -- Fiction; Superheroes -- Fiction